Microbial evaluation of wild boar carcasses coming from control culling in the subalpine Prealpi Orobie area, northern Italy - Simone Stella; Giacomo Ghislanzoni; Gualtiero Borella; Massimo Zanutto; Daniela Longhi; Cristian Bernardi; Erica Tirloni (Italian Journal of Food Safety)
This study tested 32 carcasses of control-culled wild boars in a subalpine area of Northern Italy between May and November 2021, delivered to three approved game meat establishments. Carcasses and organs were submitted to the detection of Salmonella spp., Campylobacter spp., Listeria spp., and Listeria monocytogenes; carcass surfaces were also sampled for microbial counts [total viable count (TVC), Enterobacteriaceae, Escherichia coli, coagulase-positive Staphylococci]. Campylobacter spp. was detected with high prevalence (90.9%) in the caecum as well as Listeria spp. and L. monocytogenes (37.5% and 25%, respectively), whereas only one animal harbored Salmonella spp. (3.8%). A low contamination rate was detected on the carcasses for Campylobacter spp. and Listeria spp. High TVC, Enterobacteriaceae, and E. coli counts were detected on the carcasses (5.90, 4.83 and 2.54 Log CFU/cm2, respectively). Animal sex and weight exerted a weak effect on bacterial counts; the same was observed for the culling/sampling interval. Moderately higher counts were detected in animals culled with high (>15°C) environmental temperatures. Animals shot in the abdomen showed higher counts for all the parameters except for Staphylococci, and an increasing count of enteric bacteria was observed when considering head/neck, shoulder, chest, and abdomen locations. A significant difference among the plants was observed, independently from the other factors, thus stressing the importance of the application of hygiene procedures in approved game meat establishments to limit carcass contamination.